Communication of Values to the Customer on the Functional Foods Market - Śliwińska, Irena (Studia Oeconomica Posnaniensia, 2018)
The aim of this paper is to present consumers behavior related to healthy eating, show their attitudes towards functional foods and to identify the most effective channels for conducting a dialogue with customers looking for food with a positive impact on health. This paper presents the results of original research carried out in 2017 using an original questionnaire. The research involved a group of 270 people of various ages, gender and educational levels. The following data analysis methods were used: multi response tables, Cronbach's reliability coefficient alpha, and k-means clustering. The paper indicates barriers in the communication of values related to the consumption of functional foods. This study showed that most customers have a positive attitude towards functional food, and that the most effective channel to communicate with potential clients is the Internet.